2006
DOI: 10.1063/1.2174107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excitonic diffusion on stimulated emission in nanocrystalline ZnO

Abstract: We present optically pumped emission data for ZnO, showing that high excitation effects and stimulated emission/lasing are observed in nanocrystalline ZnO thin films at room temperature, although such effects are not seen in bulk material of better optical quality. A simple model of exciton density profiles is developed which explains our results and those of other authors. Inhibition of exciton diffusion in nanocrystalline samples compared to bulk significantly increases exciton densities in the former, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Note that because the excitation intensity of 0.5 Â I th was enough higher than the threshold at the defect (about 6 Â I d_th ), broad emission spectrum already redshifted compared with that at the defect owing to the increase in the exciton density or formation of electron-hole plasma with high excitation intensity. 27 On the other hand, when we measured at the point defect (arrow 1 in Fig. 1(d)), we found that the behaviors were clearly different from the results at the defect-free sites (conventional random lasers), where a single sharp peak was observed at 381 nm (see Fig.…”
mentioning
confidence: 86%
“…Note that because the excitation intensity of 0.5 Â I th was enough higher than the threshold at the defect (about 6 Â I d_th ), broad emission spectrum already redshifted compared with that at the defect owing to the increase in the exciton density or formation of electron-hole plasma with high excitation intensity. 27 On the other hand, when we measured at the point defect (arrow 1 in Fig. 1(d)), we found that the behaviors were clearly different from the results at the defect-free sites (conventional random lasers), where a single sharp peak was observed at 381 nm (see Fig.…”
mentioning
confidence: 86%
“…The second suggested explanation is a result of weak exciton confinement due to the relatively large grain size. This is based on work suggesting that grain boundaries confine the excitons, which leads to increased n ex [24] which augments the gain.…”
mentioning
confidence: 99%
“…Since the diffusion length of free excitons in ZnO can be as large as ϳ2 m, 15,22,23 ZnO NRs with the longitudinal dimension ͑ϳ1 m͒ substantially less than the diffusion length could provide the enhanced exciton confinement and, consequently, a more efficient optical amplification process as compared to those long ͑l Ͼ 10 m͒ ZnO NWs. It has been reported that the radiative recombination via exciton-related processes ͑exciton-exciton collision, exciton-carrier collision, etc.͒ dominates the MPA-induced ASE and lasing actions in ZnO NWs under low-and intermediate-level excitation.…”
mentioning
confidence: 99%